CORRELATION DEGREES OF TUMOR INFILTRATING LYMPHOCYTES (TILs) WITH GLEASON SCORE IN PROSTATE ADENOCARCINOMA - Mitchell Theny; Irene L Parengkuan; Paul L Tahalele (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: One of the abnormalities in the prostate gland is prostate adenocarcinoma. Prostate adenocarcinoma expresses tumor antigen in the form of Prostate Specific Antigen (PSA) which will then be recognized by the immune system. The immune system then responds by infiltrating the tumor tissue. Tumor Infiltrating Lymphocytes (TILs) are defined as the infiltration of lymphocytes into the tumor microenvironment. T lymphocytes have a role in recognizing and killing tumor cells. The Gleason grading system together with serum PSA assessment and clinical staging are key in determining appropriate therapy and prognosis in prostate adenocarcinoma. The Gleason grading system is used to assess the degrees of glandular differentiation in prostate adenocarcinoma. An increase in the gleason score indicates poor gland differentiation.Purpose: To assess the correlation between the degrees of Tumor Infiltrating Lymphocytes (TILs) with gleason score in prostate adenocarcinoma.Method: This retrospective study used a correlation analytic method with a cross sectional study design that measured the degrees of Tumor Infiltrating Lymphocytes (TILs) in each gleason score of prostateadenocarcinoma that was observed once at a time. The research samples obtained from the patient's medical records included the gleason score and histopathological slides of the Transurethral Resection of Prostate (TURP) with hematoxylin eosin (HE) staining which were diagnosed as prostate adenocarcinoma according to the inclusion criteria using the non-probability total sampling method at Dr.RamelanNavy’s Central Hospital and analyzed using SPSS version 25 application.Result: Spearman correlation test to assess the correlation between the degree of stromal TILs with gleason score obtained p-value = 0.345 (p >0.05) which indicates there is nocorrelation.Conclusion: There is nocorrelation between high grade stromal TILs and high Gleason Score in prostate adenocarcinoma